Implementing Religious Moderation Using the Perspective of the Qur'an - Jamarudin, Ade; Ulya, Miftah; Abdul Fatah, Rois; Wage, Wage (KnE Social Sciences, 2022)
The face of Islam in Indonesia, which is the largest Muslim country in the world, plays an urgent moderating role in religion. The essence of Islamic teachings is moderation for its adherents. Moderation in this case is a form of religious understanding that is very much in line with the existence of Islam in Indonesia, which has a wealth of natural resources, customs, ethnicities and religions. This research aimed to provide an integrated approach to religious moderation in the life of the people in the nation using the Al-Qur’an. This research involved a literature review. The results indicated that the minside understanding of religious moderation is appropriate if it is juxtaposed with the practice of tawajun (balanced) or tawasshuth (intermediate) attitudes with the correct understanding through practicing the messages of the Qur’an. In conclusion, the word of God reflects on the importance of moderation. This includes the aspects of acknowledging the truth on the other side of disputes, upholding a tolerant attitude, respecting differences of opinion and not imposing a will by means of violence. This is described in Al-Hujarat: 13 (respecting diversity and the willingness to interact), Hud: 118-119 (conducting religious expression wisely and politely), al-Baqarah: 185 and an-Nisa’: 28. Keywords: implementing, religious moderation, Al-Qur’an